A study on prevalence of hearing impairment and ear diseases among navy personnel of the royal malaysian navy, lumut perak. - Ahmad, Mohd Ayzam (2011)
Introduction: Hearing impairment among military personnels is already well known worldwide including navy personnels. The disability will leads to psychosocial and financial dilemma but it is preventable. Objective: This study was conducted to determine the prevalence of hearing impairment and ear diseases among navy personnels of Royal Malaysian Naval, Lumut, Perak. Methodology: This is cross sectional study that had been conducted among navy personnels of Royal Malaysian Naval Lumut, Perak, from September till November 2010. Basically, two major groups involved in which they were diver and non-diver Units. Each participant was subjected to otoscopic examination and hearing tests which were Distortion Product Otoacoustic Emission (DPOAE) screening tool, Pure Tone Audiometric (PTA) and Tympanometry. Result: A total number of 233 army personnel involved in this study. The prevalence of hearing impairment among army personnel was 18.9%. There was no significant difference in percentage of hearing impairment between Diver and Non-diver unit. However, there is a significant correlation of hearing impairment with age and duration of service. Majority of them were suffering of sensorineural hearing loss specifically noise-induced hearing loss. The higher prevalence of ear disease is otitis media (0.85%) follow by impacted wax and tympanosclerosis (0.4%). Conclusion: There was high prevalence rate of hearing loss among navy personnel. While loud noise is recognized as a hazard, initiatives are required to increase use of effective preventative measures. Hearing conservation programmes are beneficial programmes that should be considered in Ministry of Defense.